2014
DOI: 10.1002/pmj.21406
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Caring—Resolving Habituation through Awareness: Supporting Meaningful Learning from Projects

Abstract: This study used Grounded Theory methodology and developed an emergent theory of Mutual Caring. The main concern was Habituation to ineffective lessons learned sharing practices. Habituation is resolved through Mutual Caring, a socially and psychologically adaptive process. Mutual Caring involves comfortable conversations, engaging/sharing, and developing self‐confidence, resulting in an enhanced wisdom pool. This paper extends the emphasis on tangible knowledge‐sharing mechanisms. Mutual Caring could lead to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 101 publications
0
8
0
Order By: Relevance
“…The MLL may pose psychological challenges and individual characteristics that motivate people to share information (Jugdev et al, 2014). Argote (2011) analyzes organizational learning considering three steps in its composition: creation, retention and transfer of knowledge.…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…The MLL may pose psychological challenges and individual characteristics that motivate people to share information (Jugdev et al, 2014). Argote (2011) analyzes organizational learning considering three steps in its composition: creation, retention and transfer of knowledge.…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…Much of the literature on learning from success or failure is based on the non-project environment. Other studies (Goffin et al, 2010;Jugdev and Wishart, 2014) identified that access to tacit knowledge was necessary, suggesting enablers for capturing and disseminating lessons, and promoting the social aspects of sharing. The social problems can become learning barriers, especially where projects separate departments of an organisation (Bartsch et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Easterby-Smith and Lyles (2011) asserted that the aspect that might take place in repetitive projects could be the replication of human resources involved in previous projects, along with the experiences exchanged and learned among project team members. This aspect resulted in the comfortable conversations and engaging/sharing, which enhance project learning (Jugdev & Wishart, 2014). Wong et al (2012) emphasized that organizational learning is regarded as essential to boosting an organization’s performance and functionality.…”
Section: Literature Reviewmentioning
confidence: 99%